Wnt-Signalwege bei kutaner Wundheilung = Wnt signaling in cutaneous wound healing - Houschyar, Khosrow Siamak; Tapking, Christian; Puladi, B.; Popp, D.; Duscher, D.; Rein, S.; Reumuth, G.; Grieb, G.; Branski, L. K.; Siemers, Frank; Lehnhardt, M.; Yazdi, A. S. (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2019)
Human skin is an efficient barrier that protects the organism from noxious substances. Wounds destroy this barrier. Wound healing is a phased physiological regeneration of the destroyed tissue that ideally leads to occlusion of a wound, in particular by regeneration of connective tissue and capillaries. The Wnt signaling pathway is a highly conserved signal transduction cascade across the animal kingdom that controls basic cellular interactions in multicellular organisms. Accordingly, through the Wnt signaling path many processes, e. g. as the balance between proliferation and differentiation or apoptosis, coordinated. Wnt signaling is activated by a wound and participates in each subsequent phase of the healing process, beginning with inflammatory control and programmed cell death, to the mobilization of stem cells within the wound. Endogenous Wnt signaling is an attractive therapeutic approach to assist in the repair of skin wounds, as the complex mechanisms of the Wnt signaling pathway have become increasingly understood over the years. This review summarizes current data to clarify the role of Wnt signaling in the wound healing process of the skin.
Available online: 13. November 2019
Gesehen am 18.01.2021